كفاءة مدرسي اللغة العربية في المدرسة الثانوية الحكومية مدينة سونجي بينوه جامبي في فهم خصائص الطلاب - ديان مارتيا س; رحماواتي; هانومي (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to identify and explore how the pedagogical competence of Arabic language teachers at Islamic Junior high school Sungai Penuh city Jambi in understanding student characteristics, the method used in this study is a qualitative case study method. The results of this study are that Arabic language teachers at Islamic Junior high school Sungai Penuh City have met 5 indicators of understanding student characteristics, namely teacher understanding of student school background, teacher understanding of student social conditions, teacher understanding of student family background, teacher understanding of student learning interests, teacher understanding of student learning difficulties. So that Arabic language teachers at Islamic Junior high school Sungai Penuh City can be stated as teachers who have pedagogical competence in understanding student characteristics.